Pengembangan Job Sheet Praktik Pemeliharaan Kelistrikan Sepeda Motor Siswa Kelas XI TBSM di SMK PIRI Sleman - Andre Gusnadi; Samsul Hadi; Alfat Khaharsyah (JURNAL VOKASI DEWANTARA (JVD), 2025)
This research aims to 1) Explain the job sheet for class XI motorbike electrical maintenance practices at PIRISleman Vocational School; 2) find out the feasibility of the job sheet for carrying out electrical maintenance for classXI motorbikes at PIRI Sleman Vocational School after it is developed. This research is research and development(R&D) with a 4-D development model (four-D models) which consists of the Define, Design, Development,Disseminate stages. development media in the form of a Job Sheet. The research subjects were class XI TBSMstudents at PIRI Sleman Vocational School. The object of this research is the Job Sheet on motorbike electricalmaintenance practices. This research and development resulted in 1) job sheet on electrical maintenance practices forJupiter Z motorbikes which contains the understanding and function of each Jupiter Z motorbike electrical system,how each component of the Jupiter Z motorbike electrical system works, wiring diagrams and how each works. -EachJupiter Z motorcycle electrical system, link/QR code for the circuit for each Jupiter Z motorcycle electrical system,inspection steps for each Jupiter Z motorcycle electrical system, and data table of inspection results. 2) the job sheeton electrical maintenance practices for Jupiter z motorbikes was declared very feasible by media experts, materialexperts and respondents/students. data obtained from the media expert validator test was 97.33% in the very goodcategory, from the material expert validator test 95.18% was in the very good category, according to students 85.47%was in the very good category.